2021
DOI: 10.1007/s13311-021-01064-z
|View full text |Cite
|
Sign up to set email alerts
|

Drug Repurposing: A Network-based Approach to Amyotrophic Lateral Sclerosis

Abstract: The continuous adherence to the conventional "one target, one drug" paradigm has failed so far to provide effective therapeutic solutions for heterogeneous and multifactorial diseases as amyotrophic lateral sclerosis (ALS), a rare progressive and chronic, debilitating neurological disease for which no cure is available. The present study is aimed at finding innovative solutions and paradigms for therapy in ALS pathogenesis, by exploiting new insights from Network Medicine and drug repurposing strategies. To id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 88 publications
(115 reference statements)
1
26
0
Order By: Relevance
“…An open-label, control study and a placebo-controlled trial with modafinil showed that this drug is safe and well tolerated and may, indeed, decrease fatigue in ALS patients (Carter et al, 2005;Rabkin et al, 2009). These results and the ones from the in silico prediction study (Fiscon et al, 2021) point to modafinil as a promising drug for ALS treatment whose beneficial effect needs to be proved in further clinical trials.…”
Section: Additional Drug Repurposing-based Therapeutic Strategies Under Investigationmentioning
confidence: 82%
See 2 more Smart Citations
“…An open-label, control study and a placebo-controlled trial with modafinil showed that this drug is safe and well tolerated and may, indeed, decrease fatigue in ALS patients (Carter et al, 2005;Rabkin et al, 2009). These results and the ones from the in silico prediction study (Fiscon et al, 2021) point to modafinil as a promising drug for ALS treatment whose beneficial effect needs to be proved in further clinical trials.…”
Section: Additional Drug Repurposing-based Therapeutic Strategies Under Investigationmentioning
confidence: 82%
“…These strategies that exploit current knowledge on disease-associated genes and disease mechanisms, protein-protein interactions, signaling networks, and drug-target interactions allow to save time and resources on the identification of candidate compounds. Accordingly, Fiscon et al (2021) exploited SAveRUNNER, a recently developed network-based algorithm for drug repurposing, which quantifies the proximity of diseaseassociated genes to drug targets to identify drug candidates for ALS. This approach allowed to identify 403 repurposable drugs that were strongly associated with the disease.…”
Section: Additional Drug Repurposing-based Therapeutic Strategies Under Investigationmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, network biology supports researchers to identify potential new treatment strategies for neurodegenerative diseases. 9 , 47 Here, we performed a network analysis on published studies that focus on fatty acid metabolism in SMA patients and mouse models, 10 KLF15 overexpression in an SMA mouse model 23 and B-Raf signaling in SMA. 22 Moreover, further proteins were added that are involved in actin and stress granules dynamics as well as the most common ALS-associated proteins ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Following the Network Medicine perspective, even the action of a drug can be interpreted as a local perturbation of the interactome, and thus, for a drug to be on-target effective against a specific disease or to cause off-target adverse effects, its target proteins should be within or in the immediate vicinity of the corresponding disease module. In recent years, several network-based approaches marrying this philosophy have been developed to aid the identification of the specific interactome neighborhood that is perturbed in a certain disease [ 12 , 13 , 14 , 15 , 16 ] and/or for the effect of a certain drug, and guide the search for therapeutic targets, identify comorbidities, as well as rapidly detect drug repurposing candidates [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. In order to quantify the interplay between drug targets and disease-specific proteins in the human interactome, in [ 17 ], the authors used a network-based drug-disease proximity measure, which prioritized associations between drugs and diseases located in the same network neighborhoods based on the average shortest paths.…”
Section: Introductionmentioning
confidence: 99%